Varför läsa litteratur – i Ryssland? Legitimeringar i ryska styrdokument - Sarsenov, Karin (Tidskrift för litteraturvetenskap, 2010)
Why Read Literature – in Russia? Justifications in Russian Steering Documents In Swedish educational debates, the question »Why study literature in school?« has been raised in connection with the theoretical development, often summarized as »the cultural turn.« The article strives to contribute to this discussion by comparing the development of educational discourse in Sweden, as analyzed by Magnus Persson, with the parallel development in Russia. Here, literature is a compulsory and separate school subject from the fifth to the eleventh grade. Since 1991, the educational system has undergone a radical reform, but the number of hours devoted to literature has not changed significantly. This would suggest that literature still is perceived as an important means of incorporating children into the national and political community. The target of this study is to identify authorities’ specific aims with devoting so much time to literature in school, as well as to elucidate in what way literature is to achieve these aims. Russian guidelines for the development of literature curricula published in the years 1991-2010 are examined to see just how literature is legitimated as a secondary school subject. Based on this material, the article draws conclusions about the rhetorical practices and ideological development of curricular discourse, its relationship to Soviet educational thought and the extent to which the cultural turn has influenced this sphere. The findings of Örjan Torell, a pioneering scholar in Russian-Swedish comparative educational studies, are also scrutinized and questioned on the basis of methodology.